Filtros e barreiras no acesso à justiça norte-americana: as doctrines of justiciability / Filters and barriers in access to american justice: the doctrines of justiciability - Neto, Eugênio Facchini (REVISTA QUAESTIO IURIS, 2016)
Trabalho enviado em 23 de setembro de 2015. Aceito em 06 de dezembro de 2015. DOI: 10.12957/rqi.2016.18790 Resumo: O artigo aborda as denominadas Doctrines of Justiciallity, como são chamadas, nos Estados Unidos, um conjunto de ideias (dentre as quais destacam-se a standing to sue, a ripeness, a mootness e a political question, que são utilizadas como filtros ou barreiras ao acesso à justiça. Em nome dessas figuras, veda-se o cesso á justiça sob o argumento de que determinadas pretensões não devem, ou não podem, ou ainda não podem ou não podem mais, serem enfrentadas em uma ação judicial. Busca-se com isso, a partir da interpretação da constituição daquele país, estabelecer quais são as controvérsias e casos são apropriados para uma resolução judicial. O estudo procura demonstrar coo instrumentos técnicos são usados para justificar determinadas opções ideológicas para não envolver o Poder Judiciário em temas de grande interesse social ou político. Palavras-chave: Direito processual norte-americano. “Doutrinas de justiciabilidade” - Standing to sue – Ripeness – Mootness – Questão política. Abstract The article discusses the so-called doctrines of justiciability, as they are called in the United States, a set of ideas (among which stand out the standing to sue, ripeness, mootness and political question) that are used as filters or barriers to access to justice. In other words, invoking one of these figures, prevents access to Justice under the argument that certain claims should not, or cannot, or cannot yet or can no longer be object of a lawsuit. Through the interpretation of the American constitution, it searchs to establish what are the controversies and cases that are appropriate to be decided in a judicial context. The study seeks to demonstrate how technical instruments are used to justify certain ideological choices, as not to involve the Judiciary in topics of great social or political interest. The work is based on american and comparative law bibliographic references and on american jurisprudence. It seeks to demonstrate, in conclusion, that the decision not to decide a question is already, in itself, a decision, usually conservative, although under the mantle of neutrality. Keywords: Doctrines of Justiciability - Standing to sue – Ripeness – Mootness - Political question